Measurement of Generic Skills of Students: A Systematic Literature Review - Siska Merrydian; Yetti Supriyati Saefudin; Anan Sutisna (Postgraduate, University of Mataram, 2023)
One of the talents that students must have to face rapidly developing global problems is generic skills. Therefore, it becomes important to measure generic skills in students. The method used in this study is a systematic literature review using the PRISMA diagram. The database used to search for literature utilized two digital libraries, namely Google Scholar and Scopus. In order to make the selected literature relevant, the search used the keyword